Estudo do mecanismo de ação antinociceptivo e avaliação histopatológica cerebral do (S)-(-)-álcool perílico em camundongos - Benedito, Rubens Batista (2013)
The perillyl alcohol (p-mentha-1,8-diene-7-ol) is a member of the family of monoterpenes found in plants of the genus Lavandula, Mentha, Cymbopogon, among others. It is known that perillyl alcohol (AP) has antinociceptive activity, but its mechanism of action remains unknown. In the present study was investigated the possible mechanism of action of PA using pharmacological antagonists and in vitro, and evaluated the histological level neurotoxicity in the hippocampus and striatum. The test of writhing induced by acetic acid was the protocol of choice for testing the monoterpene at a dose of 100 mg/kg against antagonists. The results show a reversal of the antinociceptive effect of PA (PA 3,4 ± 1,7 writhing) after pretreatment with naloxone (NLX+PA 10,4 ± 2,3 writhing) indicating the participation of the opioid system in its mechanism of action. Unlike naloxone, antagonists, muscarinic (atropine), adenosinergic (caffeine), dopamine (sulpiride), L-arginine - L-NNA and glibenclamide, were not able to reduce the effect of the PA front abdominal writhing. In the evaluation of in vitro antioxidant activity of the PA, three methodologies were employed, one to evaluate the effect of PA on lipid peroxidation in TBARS test and the other two to investigate its action as substance radical scavenging OH and NO. In all tests, the PA showed antioxidant activity, reducing by 70% the production of free radicals. As for histopathological evaluation, the PA did not cause significant tissue changes in both brain areas studied. Therefore, the results obtained in this study demonstrate that perillyl alcohol has an antinociceptive effect mediated by the opioid system and antioxidant mechanisms, without the direct participation of muscarinic systems, adenosinergic, dopaminergic, K+ATP channels and via L-arginine nitric oxide. The monoterpene also did not show significant neurotoxicity.